The art of control engineering - Dutton, Ken.; Barraclough, Bill.; Thompson, Steve (Harlow [England] : Addison-Wesley, 1997)
This book is about: An introduction to control system modelling; System responses, stability and performance; System identification and modelling revisited; ...
Keywords: Engineering; Automatic control; Automatic control